S88 Electron Tomography Detects Ultrastructural Abnormalities In Patients With Pcd Due To A Dnah11 Defect. (10th November 2014) - Kwan, R; Burgoyne, T; Dixon, M; Patel, M; Scully, J; Onoufriadis, A; Hogg, C; Mitchison, HM; Shoemark, A
Abstract : Primary Ciliary Dyskinesia (PCD) is a genetically heterogeneous condition. characterised by impaired mucociliary clearance and chronic sino-pulmonary disease. Over 30 causative gene mutations resulting in dysfunctional ciliary motility and structure have been identified. Ciliary ultrastructure examined by Transmission Electron Microscopy (TEM) is currently the diagnostic gold standard. Patients with mutations in the gene DNAH11 have a hyperfrequent ciliary beat and clinical symptoms of PCD. Diagnosis of a DNAH11 defect by TEM is difficult due to apparently normal ciliary ultrastructure. The electron tomography technique, an extension of TEM, produces 3D models of cilia with superior resolution. The aim of this study was to determine if electron tomography can detect ultrastructural abnormalities in patients with DNAH11 defects. Immunofluorescence by specific antibodies for DNAH11 showed localisation to the proximal portion of cilia. Proximal cilia cross sections from araldite embedded nasal brush biopsies were examined. Dual axis tomograms were collected on a Philips CM200 electron microscope. The data were analysed using IMOD software and averaged using PEET. Electron tomography and averaging of cilia cross sections indicated a deficiency in the outer dynein arm, consistent across all patients with a DNAH11 defect (n = 5) compared to healthy controls (n = 3) and patients with PCD due to a defect of the central pair or nexin link (n = 3) (Figure 1 ). A reduction in outer dynein arm volume of 30% was identified compared to healthy and PCD controls. In conclusion, a mutation in DNAH11 results in a subtle abnormality in ultrastructure. The defects are specific to the 'forearm' of the outer dynein arm and only detectable at the base of the cilium where DNAH11 is located. Electron tomography is highly effective in visualising this defect.